Market Reactions to Quest for Decentralization and Independence: Evidence from Catalonia - Vincenzo Galasso (Center for Economic Studies and ifo Institute (CESifo), 2020)
Regions seeking more autonomy aim at making less (or no) fiscal transfers to central governments and at reaching more (or total) control on regional spending. However, decentralization may lead to joint central-regional responsibility that increases regulatory uncertainty regarding the bureaucratic and fiscal burdens on firms. Moreover, quests for independence create political uncertainty. To evaluate economic costs and benefits for firms from decentralization or independence, we analyze the Catalan-Spanish negotiation leading to the 2006 Catalan Statute and the more recent quest for independence. We use an event approach methodology to estimate the immediate stock market reaction to new events. Our results suggest that the stock market had a conservative reaction both to more decentralization and to independence. The approval of the Catalan Statute was associated with negative returns for Catalan firms, particularly in the tradable sector. These firms later benefitted from the partial reversal imposed by the Spanish Constitutional Court ruling. The large increase in the political uncertainty that emerged at the referendum day had a strong negative effect on all Catalan firms and on Spanish firms in the tradable sector. This uncertainty was partially reduced, when the Spanish Senate rejected the declaration of Catalan independence. Markets reacted positively, with Catalan, but also Spanish, firms in all sectors posting large gains that largely compensated the previous losses.
Keywords: H77; G14; 330; independence; decentralization; event approach